Historical Analysis of the Development of Hadith Studies in the Sham Region in the Second Century Hijri - Amni Al (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2026)
Abstract This study examines the development and spread of Hadith in the Sham region during the second century Hijri, using historical approaches and qualitative library research methods. The region of Sham was one of the important centers of the transmission and development of hadith science in the early days of Islam, supported by the presence of the companions of the Prophet Muhammad (saw) and by the role of the great scholars who spread Hadith in this region. This study found that companions disseminated the Prophet's hadiths through madrasas (Islamic educational institutions), using both oral and written methods. Among the scholars who pioneered the spread of Hadith in this region were Muadz bin Jabal, Abu Darda, and Ubadah bin Shamit. At this time, the codification of Hadith was also carried out by Muhammad bin Syihab al-Zuhri on the order of the caliph Umar bin Abdul Aziz. These books were then distributed to several regions. Abstrak Penelitian ini membahas perkembangan penyebaran hadis di kawasan Syam pada abad ke II Hijriah melalui pendekatan historis dan metode studi pustaka (library research) kualitatif. Kawasan Syam merupakan salah satu pusat penting transmisi dan perkembangan ilmu hadis pada masa awal Islam, yang didukung oleh keberadaan sahabat-sahabat Nabi Muhammad Saw, serta peran ulama-lama besar yang menyebarkan hadis di wilayah ini. Hasil penelitian ini menemukan bahwa proses penyebaran hadis-hadis nabi dilakukan oleh para sahabat melalui madrasah (lembaga pendidikan keislaman) dengan pembelajaran lisan dan tulisan. Di antara tokoh ulama yang menjadi pelopor penyebaran hadis di wilayah ini adalah Muadz bin Jabal, Abu Darda, dan Ubadah bin Shamit. Pada masa ini juga dilakukan pengkodifikasian hadis oleh Muhammad bin Syihab al-Zuhri atas perintah khalifah Umar bin Abdul Aziz. Kitab-kitab ini kemudian disebarkan ke beberapa daerah.